Melampaui Tradisi: Meningkatkan Kualitas Sumber Daya Manusia untuk Pariwisata Berkelanjutan di Desa Ngadas, Kabupaten Malang - Yudi Harianto Cipta Utama; Sari Dewi Poerwanti (Journal of Urban Sociology, 2023)
Desa Ngadas in Malang Regency is an area with promising potential as a tourist destination. It has been recognized as a traditional tourism village that is able to attract both domestic and foreign tourists. In the development of its tourism sector, the aspect of human resources is crucial to be discussed. This paper aims to analyze the quality of human resources in Desa Ngadas through several aspects, namely health, education, socio-culture, economy, and community empowerment. The research method used is descriptive qualitative, involving 10 informants selected through purposive sampling technique. The results of this study depict the population's socio-cultural influence of the Tengger culture, which is closely tied to the traditions of the Tengger tribe. In terms of human quality, including nutrition and food, health, education, income, empowerment, independence, social environment, and economy, all depict the distinctive Tengger characteristics, with the majority working as farmers as the main alternative occupation, providing relatively high income for those who own agricultural land, while their social education is relatively low. The factors influencing the improvement of the capacity and quality of human resources are more dominant due to relatively low education and traditional mindsets.Keywords: human resources; tourism villages; village community